State of World Population 2008 - United Nations Population Fund (United Nations, 2008)
The State of World Population 2008 demonstrates that an appreciation for cultures and values is a critical but sometimes overlooked aspect of successful development strategies. It shows how culture can strengthen and validate human rights perspectives and enable their broader acceptance, ownership and realization. The report argues that synergy between the global human rights agenda and cultural aims can help advance the Millennium Development Goals and contribute to ending extreme poverty.